Legitimating telefantasy: exploring the value of telefantasy through television history - Dervish Ali, Erdem (2020)
This thesis explores the changing perceptions of telefantasy’s legitimacy over two periods of television, TV I (also known as the network era, encompassing the medium’s creation to the 1980s) and TV II (also known as the multi-channel transition, lasting from the end of TV I to the early 2000s) in the United States. The thesis argues that telefantasy’s cultural value changes throughout time. It demonstrates that time and place play a significant role in the legitimacy of a product, its value influenced relatively to certain textual and paratextual factors. The thesis contends that the perception and construction of telefantasy’s legitimacy depends on factors both from outside of a telefantasy programme, especially industrial factors, and from features found within a television show itself, like its genre. Such factors are also temporally specific as, like cultural value, the television industry and its discernment of its spectators’ tastes determine the value of their products, and these evaluations change over time. Chapter 1 discusses academic concepts of legitimacy and relates them to the media and to television. It builds its construction of value on the theoretical bases established by Pierre Bourdieu’s (1984) notions of distinction and cultural hierarchies, Shyon Baumann’s (2007) functional design for film, and Michael Z. Newman and Elana Levine’s (2012) exploration of televisual legitimacy. These and other theoretical concepts are then used to establish a list of legitimating criteria for telefantasy. Chapter 2 presents a background of the television industry during TV I, with a similarly themed Chapter 5 detailing TV II. Following these historical frameworks, chapters 3, 4, 6, and 7 offer an in-depth investigation of the case studies within each period of television, The Twilight Zone (CBS, 1959-1964) and Star Trek (NBC, 1966-1969) in TV I, and The XFiles (Fox, 1993-2002) and Buffy the Vampire Slayer (The WB, 1997-2001, UPN, 2001-2003) in TV II. These chapters analyse journalistic discourses about the programmes from the perspective of the legitimating criteria presented in Chapter 1, relating the changes in perception and construction of legitimacy to the relevant historical period. The thesis overall details the ways in which the legitimating criteria changed over time and reveals the impact that the genres within telefantasy, like science fiction, horror, and fantasy, have in shaping perceptions of value, a unique and unexplored way of understanding the cultural value of the medium.